2015
DOI: 10.1007/s10484-015-9303-z
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Amylase as a Measure of Sympathetic Change Elicited by Autogenic Training in Patients with Functional Somatic Syndromes

Abstract: The aim of this study was to discuss the effect of autogenic training (AT) on patients with functional somatic syndrome (FSS) using salivary amylase, the skin temperature of the finger, subjective severity of symptoms, and psychological characteristics as measures. We assessed 20 patients with FSS and 23 healthy controls before and after AT. Baseline levels of salivary amylase prior to an AT session were significantly higher in the FSS group than in the control group. However, this difference was not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
3
7
0
1
Order By: Relevance
“…This indicates that the sympathetic nervous system is strained in patients with FSS. This finding is in agreement with our previous study [28]. Moreover, the SAMY level under mental stress in patients with FSS was significantly higher than that in healthy controls in our previous study [18].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This indicates that the sympathetic nervous system is strained in patients with FSS. This finding is in agreement with our previous study [28]. Moreover, the SAMY level under mental stress in patients with FSS was significantly higher than that in healthy controls in our previous study [18].…”
Section: Discussionsupporting
confidence: 94%
“…In our previous study, the SAMY level decreased during the first AT session in the control group, suggesting that AT is a helpful method of relaxation for healthy people [28]. In the present study, we confirmed this effect of relaxation not only in the first AT session but also after continuing AT for 4 or 8 weeks.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations